2019
DOI: 10.1111/ijpo.12514
|View full text |Cite
|
Sign up to set email alerts
|

Weight‐based victimization among sexual and gender minority adolescents: Findings from a diverse national sample

Abstract: Summary Objectives Children and adolescents with overweight and obesity are vulnerable to weight‐based victimization. Research on weight‐based victimization and sexual identity have been largely isolated from one another; little is known about the nature of weight‐based victimization in sexual and gender minority (SGM: eg, lesbian, gay, bisexual, and transgender) youth. Our study is the first to examine the nature, extent, and sources of weight‐based victimization in a large sample of SGM adolescents. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 37 publications
2
45
0
1
Order By: Relevance
“…For example, SM men and those who identify as “Other” sexual orientation may have an increased risk of being underweight and thus were likely missed in our WW sample. Recent evidence indicates that weight‐based victimization is prevalent across diverse sexual and gender identities of youth ; future research examining weight stigma in SM adults should include individuals with emerging sexual identities (e.g., asexual, pansexual), as well as more established sexual identities, and assess weight stigma across diverse gender and racial/ethnic identities. Although our study included multiple measures of weight stigma, we did not assess psychological or behavioral responses to interpersonal sources of stigma, which could help inform the relationship between weight stigma and health in future research.…”
Section: Discussionmentioning
confidence: 99%
“…For example, SM men and those who identify as “Other” sexual orientation may have an increased risk of being underweight and thus were likely missed in our WW sample. Recent evidence indicates that weight‐based victimization is prevalent across diverse sexual and gender identities of youth ; future research examining weight stigma in SM adults should include individuals with emerging sexual identities (e.g., asexual, pansexual), as well as more established sexual identities, and assess weight stigma across diverse gender and racial/ethnic identities. Although our study included multiple measures of weight stigma, we did not assess psychological or behavioral responses to interpersonal sources of stigma, which could help inform the relationship between weight stigma and health in future research.…”
Section: Discussionmentioning
confidence: 99%
“…More information regarding the study design can be found elsewhere. 21,22 In total, 20,306 eligible participants started the survey. Among those, 3006 (14.8%) participants did not complete the initial demographic information and were excluded from all data analyses.…”
Section: Study Design Participant Recruitment and Data Cleaning Promentioning
confidence: 99%
“…These studies document widespread instances of personal victimization as well as second-hand observations of peers being victimized or general anti-LGBQ epithets (e.g., Bthat's so gay^; Birkett et al 2009;Bucchianeri et al 2016;Kosciw et al 2018;Ybarra et al 2015). However, a recent GLSEN survey indicated that as many as 25% reported bias-based bullying and harassment due to other sources of social stigma as well (Kosciw et al 2018), andPuhl et al (2019) documented that over half of LGBTQ youth report weight-based teasing and victimization at home and/or school. Given that many LGBQ youth also have one or more additional stigmatized 1 Variations in acronyms reflect differences in study samples.…”
Section: Bias-based Bullying Victimization Among Lgbq Youthmentioning
confidence: 99%